2012
DOI: 10.1158/0008-5472.can-12-0157
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Multipotent Progenitors with a Basal Differentiation Bias during Aging of Human Mammary Epithelia

Abstract: Women over 50 years of age account for 75% of new breast cancer diagnoses, and the majority of these tumors are of a luminal subtype. Although age-associated changes, including endocrine profiles and alterations within the breast microenvironment, increase cancer risk, an understanding of the molecular mechanisms that underlie these observations is lacking. In this study, we generated a large collection of normal human mammary epithelial cell strains from women aged 16 to 91 years, derived from primary tissues… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
148
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 101 publications
(173 citation statements)
references
References 48 publications
(62 reference statements)
23
148
2
Order By: Relevance
“…To do so, we used uncultured primary cells isolated from human reduction mammoplasty tissue. Compared with the fourth-passage primary cells used in our previous experiments, uncultured primary cells have elevated levels of cellular heterogeneity in a variety of cell-surface markers (15,27). Consistent with underlying variability in the energetics of their cellular interfaces, we found that pure populations of uncultured luminal or myoepithelial cells formed aggregates with more variable and overlapping circularity than fourth-passage primary cells (Fig.…”
Section: Self-organization Of the Mammary Gland Is Robust To Highly Vsupporting
confidence: 85%
“…To do so, we used uncultured primary cells isolated from human reduction mammoplasty tissue. Compared with the fourth-passage primary cells used in our previous experiments, uncultured primary cells have elevated levels of cellular heterogeneity in a variety of cell-surface markers (15,27). Consistent with underlying variability in the energetics of their cellular interfaces, we found that pure populations of uncultured luminal or myoepithelial cells formed aggregates with more variable and overlapping circularity than fourth-passage primary cells (Fig.…”
Section: Self-organization Of the Mammary Gland Is Robust To Highly Vsupporting
confidence: 85%
“…[45][46][47] Our M87A/85 media support proliferation of pre-stasis HMEC with progenitor lineage markers, and allow robust proliferation prior to p16 upregulation. 10,48 Such lower stress/p16-inducing conditions may be reflective of early stage carcinogenesis in vivo, if unstressed progenitor cells are initial targets.…”
Section: Discussionmentioning
confidence: 99%
“…Cultured HMEC have been employed in a wide variety of studies examining the normal processes governing growth, differentiation, aging, and senescence, and how these normal processes are altered during immortal and malignant transformation [4][5][6][7][8][9][10][11][12][13][14][15]16 . The effects of growth in the presence of extracellular matrix material, other cell types, and/or 3D culture can be compared with growth on plastic 5,15 .…”
mentioning
confidence: 99%